(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The work in this study is focused on investigation of the tribological behavior of ductile cast iron with nanosized particles: titanium nitride TiN; titanium nitride 30% + titanium carbonitride 70% (30%TiN+70%TiCN). The ductile cast iron composition is: Fe-3,55C-2,67Si-0,31Mn-0,009S-0,027P-0,040Cu-0,025Cr-0,08Ni-0,06Mg wt%. Before the addition to the melt nanosized particles were coated with nickel by the electroless nickel deposition method EFFTOMNICKEL .The nickel coating on the nanosized particles ensures their wetting in the melt as well as their uniform distribution into the cast. The optical and quantity metallographic observations and wear test are performed to study the influence of the nanoparticle additives on the cast iron tribological properties. It is observed that the quantity proportion changes between pearlite, ferrite and graphite phase in the cast iron structure. The graphite shape is retained the same, but the nanosized additives decrease the average diameter of the graphite spheres Dmid and increase the quantity of the graphite phase in the structure of ductile cast irons. The cast iron wear resistance in the presence of nanosized additives of (TiN+TiCN) and TiN increases to 55–69% in comparison to wear resistance of the cast iron without nanoparticles.